SMART CLASS PROTOTYPE USING INTERNET OF THINGS TECHNOLOGY AT PACITAN STATE COMMUNITY ACADEMY - Tri nugroho, Kurnianto; Julianto, Bagus; Rengga Tisna, Dhodit; Copernikus Andaria, Alex (Journal of Computer Science and Technology (JCS-TECH), 2025)
This study aims to overcome the causes of wasteful electricity usage in the study room and the swelling of electricity bills that must be paid due to user negligence in turning off existing electronic devices and the length of time to start lectures because they have to turn on electronic devices one by one, then the conventional control system in the study room can be updated to be semi-automatic. The system that can be created is a smart class, where a smart class is a system for accessing electricity using a smartphone or by attaching the RFID card of a lecturer who enters the class or security staff to the RFID reader. After the system reads the appropriate ID number, the electrical system in the study room can be accessed. The system will automatically disconnect after 2 minutes the RFID card is removed from the RFID reader or by accessing the blynk application on the smartphone. This study uses an experimental research method that begins with design analysis, design, implementation to testing. The results of the system test show that the smart class system is successful in all processes, both turning on and off electronic devices using RFID and the blynk application or monitoring electronic devices via smartphones effectively.